Estudio del tratamiento de la información periodística acerca de la problemática de la minería que publican los diarios La Hora y Crónica en la provincia de Loja. Período enero 2022 – enero 2023. - Valdes Córdova, Eber Anderson (2024)
The way in which the media broadcast news is mediated by the journalistic treatment they give to it, through the codes of ethics that the institution maintains and the work of the journalist on the scene, which is why this research focused on analyzing how the media, La Hora newspaper and Crónica newspaper in the province of Loja present information about the problem of mining in their news content. Through the objectives of the study, it was intended to analyze the news on mining presented by the two newspapers in question and determine in which genres and areas they are classified and whether the information is presented objectively and impartially, thus allowing the generation of strategies to provide solutions to the irregularities that occur in the broadcasting of news. The research was developed under the qualitative methodological approach that allowed obtaining information in the established period of time, on the news with content on mining in the province of Loja issued by the aforementioned newspapers, with the use of tools and techniques for data collection, such as observation sheets and content analysis that were key to the development and achievement of the objectives and the study as such. With the results of the research, it was determined that the two media outlets do not assume full responsibility for the quality of the information they present in this regard, since there is little information on how mining extraction companies handle the resources of the southern region and the little news content that exists on this subject is not very detailed, thus showing shortcomings in journalistic action and in the ethical treatment of the information. Keywords: journalistic treatment; mining; journalistic ethics; environmental journalism; Loja.